Living donor liver transplantation for Echinococcus Alveolaris: single‐center experience. Issue 8 (3rd July 2015) - Ozdemir, Fatih; Ince, Volkan; Barut, Bora; Onur, Asim; Kayaalp, Cuneyt; Yilmaz, Sezai
<x xml:space="preserve">Abstract</x> Echinococcus alveolaris (EA) causes a hepatic zoonotic infection and behaves like a malignant tumor during invasion. Liver transplantation (LT) is the only curative treatment option for this unresectable disease. Here, we share our experience with living donor liver transplantation (LDLT) due to EA from the time between March 2002 and November 2014 at the Liver Transplantation Institute of İnönü University. Ten patients (mean age, 38.6 years) undergoing LDLT because of unresectable EA were evaluated preoperatively, and the operative and follow‐up data were analyzed retrospectively. The mean time interval between diagnosis and LT was 27 months. The mean operation time and mean intraoperative blood requirement were 613 minutes and 4 units of packed red blood cells, respectively. Diaphragmatic resections were performed in 3 patients, and vena cava replacement was performed in 2 patients because of difficulties in removing the extended disease. The local recurrence and distant metastasis rates were 10% and 20%, respectively. The mean survival time was 19.5 months (range, 0‐54 months), and the mortality rate was 30%. Unresectable hepatic alveolar echinococcosis is a rare indication for LT and presents some technical difficulties during surgery because diaphragmatic resection, vascular reconstruction, or multiple blood transfusions may be needed. LDLT can be performed successfully in patients with this rare infectious disease, with careful follow‐up for potential recurrence and metastasis and administration of low‐dose immunosuppressive agents. Liver Transpl 21:1091‐1095, 2015. © 2015 AASLD.